High performance, All solid state, flexible Supercapacitor based on Ionic liquid functionalized Graphene. (1st March 2015) - Ujjain, Sanjeev Kumar; Sahu, Vikrant; Sharma, Raj Kishore; Singh, Gurmeet
Graphical abstract: Schematic: (a) Digital photograph showing f-graphene supercapacitor. (b) Schematic of the supercapacitor structure consisting of two symmetrical f-graphene electrodes and gel polymer electrolyte cum separator & (c) Schematic representation of functionalization of the f-graphene. Highlights: Ionic liquid [BMIM][BF4 ] (1-butyl-3-methylimidazolium tetrafluoroborate) modified reduced graphene oxide ( f -graphene) is investigated as supercapacitor electrode. Symmetric supercapacitor based on f -graphene//[EMIM][BF4 ]:PVdF-HFP gel polymer electrolyte// f -graphene is fabricated. Proposed supercapacitor delivers very high energy density 92 Wh/kg with a power density 33 kW/kg at 0.5 A/g. Ultra short relaxation time 2.4 ms signifies fast energy delivery at relatively high power for the proposed supercapacitor cell. Abstract: A high-performance all solid state supercapacitor incorporating ionic liquid [BMIM][BF4 ] (1-butyl-3-methylimidazolium tetrafluoroborate) modified reduced graphene oxide ( f -graphene) electrode is fabricated. [EMIM][BF4 ] (1-ethyl-3-methylimidazolium tetrafluoroborate): [PVdF-HFP] Poly(vinylidenefluoride hexafluoropropylene was used as gel polymer electrolyte. Presence of imidazolium cations over graphene sheet generated a surface charge that enables large accessible surface area wettable by gel polymer electrolyte. Supercapacitor device assembled using f -graphene electrode and [EMIM][BF4 ]:PVdF-HFP gel polymer electrolyte exhibit very high energy density 92 Wh/kg with a power density 33 kW/kg at 0.5 A/g. The energy density demonstrates 57% retention with power density 218 kW/kg on increasing current density to 6 A/g. The relaxation time constant (τo) for f -graphene//gel polymer electrolyte// f -graphene cell assembly was calculated to be 2.4 ms, which is much lower than any existing EDL system, indicating fast energy delivery at relatively high power. Fabricated solid state, flexible supercapacitor demonstrate high capacitance ∼242 F/g at 5 mV/s and showed excellent galvanostatic charge/discharge cycling stability (capacitance retention > 90% up to 12, 000 cycles).